(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The following article deals with the question of how Chinese martial arts as part of traditional culture survived into modern times and created a worldwide interest. The paper focuses on the process of modernization of Chinese martial arts against the background of massive social transformations in China during the 19th century. It analyzes different aspects of the self-assertion process of martial arts and points out consequences of the radical break with the traditional system.